Development of dry electrodes for electroencephalography by using a SLA-type 3D printer - Nishida, Shin-Ichiro; Araki, Nozomu; KIMURA, Masaya; Nakatani, Shintaro (Transactions of Japanese Society for Medical and Biological Engineering, 2020)
In recent years, Brain-Computer Interface (BCI) has been catching much attention. EEG has been bringing remarkable results on the communication with those patients with ALS, locked-in syndrome and rehabilitation against patients with cerebrovascular disease. However, wet electrodes used on EEG set on the patient's head directly and it could cause mental dissatisfaction on him. A solution to this problem is to use pasteless dry electrodes but tend to have higher noise and costly. Fabricating a dry electrode of any shape in a short time at low cost by using an SLA type 3D printer with high spatial resolution, the purpose of the study is to measure EEG without conductive gel, and we consider appropriate electrode shape. Using the fabricated electrode, we measure the change of alpha-wave that predominates while the eyes are closed.